2017
DOI: 10.1093/hmg/ddx386
|View full text |Cite
|
Sign up to set email alerts
|

Cx32 hemichannel opening by cytosolic Ca2+ is inhibited by the R220X mutation that causes Charcot-Marie-Tooth disease

Abstract: Mutations of the GJB1 gene encoding connexin 32 (Cx32) cause the X-linked form of Charcot-Marie-Tooth disease (CMTX1), a demyelinating peripheral neuropathy for which there is no cure. A growing body of evidence indicates that ATP release through Cx32 hemichannels in Schwann cells could be critical for nerve myelination, but it is unknown if CMTX1 mutations alter the cytosolic Ca2+-dependent gating mechanism that controls Cx32 hemichannel opening and ATP release. The current study uncovered that loss of the C-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 85 publications
9
41
0
Order By: Relevance
“…The relevance of connexins and their tightly regulated function is highlighted by their implication in pathological states of completely different character, such as cancer (Tsai et al, 2018 ), inflammation (Li et al, 2018 ), and neurodegenerative diseases (Belousov et al, 2018 ). For this reason, modulation of connexin hemichannels is becoming increasingly interesting for the treatment of several diseases including Alzheimer Disease (Yi et al, 2017 ), skin disorders, or X-linked Charcot Marie Tooth disease (Sáez and Leybaert, 2014 ; Carrer et al, 2017 ; Xu et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The relevance of connexins and their tightly regulated function is highlighted by their implication in pathological states of completely different character, such as cancer (Tsai et al, 2018 ), inflammation (Li et al, 2018 ), and neurodegenerative diseases (Belousov et al, 2018 ). For this reason, modulation of connexin hemichannels is becoming increasingly interesting for the treatment of several diseases including Alzheimer Disease (Yi et al, 2017 ), skin disorders, or X-linked Charcot Marie Tooth disease (Sáez and Leybaert, 2014 ; Carrer et al, 2017 ; Xu et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In 1997, Oh et al (Oh et al, 1997 ) hypothesized that the primary defect underlying CMT1X neuropathy in the presence of Cx32 mutants forming electrically conductive channels is the lower permeability of GJ channels to cAMP, which is involved in myelin homeostasis in SCs (LeBlanc et al, 1992 ). We have recently demonstrated that this theory is unlikely, at least with regard to the most studied CMT1X mutant (R220X; Carrer et al, 2018 ). Indeed, lack of Cx32 GJs in myelinating SCs does not appear to cause a slower radial diffusion of low molecular weight dyes along the myelin sheath of Cx32-null mouse with respect to the WT due to the presence of other connexins forming GJ channels (Balice-Gordon et al, 1998 ).…”
Section: Discussionmentioning
confidence: 98%
“…Most of these studies were limited to testing only GJ channel electrical conductance, so minimal information is available about specific permeability to important molecules up to 1 kDa (e.g., second messengers), which could explain why some mutants appear as “functional” with respect to the WT. Limited information is also available about gating/permeability dysfunction of mutant Cx32 hemichannels, analyzed in the following studies: S26L (Mones et al, 2014 ), S85C (Abrams et al, 2002 ), D178Y (Gómez-Hernández et al, 2003 ), E208K-Y211X-R215X-R215W-R215Q-C217X (Castro et al, 1999 ), R220X (Castro et al, 1999 ; Carrer et al, 2018 ), F235C (Liang et al, 2005 ), R238H-R265X-C280G-S281X (Castro et al, 1999 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 135 Numerous reports since then have demonstrated the sensitivity of connexin HCs to extracellular Ca 2+ , which are believed to keep connexin HCs in a closed state at physiological Ca 2+ levels. 136 138 In contrast, Panx HCs are not gated by external Ca 2+ , 139 and the mechanical sensitivity of pannexin HCs was not noted until 2004, when single-channel currents were elicited by changes in pressure imposed pneumatically upon membrane patches of Xenopus oocytes expressing Panx1. 140 Since then, mechanosensitive purinergic signaling pathways, including pannexin-mediated ATP release, have been demonstrated in many cell types in response to mechanical stimuli.…”
Section: Pannexins Mechanical Signaling and The Cytoskeletonmentioning
confidence: 99%